2012
DOI: 10.1517/17425255.2012.698261
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of oral drug absorption processes in children

Abstract: Clinicians should bear in mind the ontogeny of oral drug absorption processes when prescribing oral drugs to children. The authors' review shows large information gaps on almost all drug absorption processes. It is important that more knowledge is acquired on intestinal transit time, intestinal pH and the ontogeny of intestinal drug-metabolizing enzymes and drug transporter proteins. Furthermore, the ultimate goal in this field should be to predict more precisely the oral disposition of drugs in children acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 99 publications
0
67
0
Order By: Relevance
“…Understanding changes in gastric emptying with age is important both clinically in terms of the pathophysiology of disease and for predicting the absorption of orally administered drugs 32. Gastric emptying is a primary determinant of the rate at which drugs are presented to the small intestinal mucosa for absorption and, along with a multitude of other age related changes, may influence the design of suitable dosage forms for administration to neonates and infants.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding changes in gastric emptying with age is important both clinically in terms of the pathophysiology of disease and for predicting the absorption of orally administered drugs 32. Gastric emptying is a primary determinant of the rate at which drugs are presented to the small intestinal mucosa for absorption and, along with a multitude of other age related changes, may influence the design of suitable dosage forms for administration to neonates and infants.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, their applicability towards pediatric populations, who are developmentally distinct in terms of gastrointestinal anatomy/physiology, remains questionable. Of most interest are children belonging to the youngest age groups (i.e., neonates and infants) who display the greatest developmental differences in comparison to adults (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Some PEPT1 substrates are dosed to children even very early in life. Considering the wide age-related variation in the processes affecting oral drug absorption-including gastric pH, gastric motility, and drug metabolizing enzyme activity-age-related changes in membrane transporters are also very likely (Mooij et al, 2012). A previous study by our group Mooij et al (2014) showed transporter-dependent maturation in gene expression in young infants for MDR1, MRP2, and OATP2B1, but overall data on the intestinal expression of membrane transporters during growth and development are very scarce (Brouwer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%